2011
DOI: 10.2478/v10059-011-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

The Maslach Burnout Inventory-General Survey: validation across different occupational groups in Poland

Abstract: This paper concerns the psychometric evaluation of the Polish version of a self-report

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 18 publications
2
30
0
8
Order By: Relevance
“…A three factored structure comprised of 15 items was yielded as a result of CFA made for MBI-GS. This result yielded shows consistency with the results of similar research verifying MBI-GS's three factored structures in literature Langballe, Falkum, Innstrand & Aasland, 2006;Chirkowska-Smolak & Kleka, 2011). Moreover, it is observed that the correlation values found to range between .19 and .66 between MBI-GS's sub factors are similar to the research results in the literature Taris, Schreurs & Schaufeli 1999;Bakker, Demerouti & Schaufeli, 2002;Chirkowska-Smolak & Kleka, 2011).…”
Section: Result Discussion and Proposalssupporting
confidence: 91%
See 1 more Smart Citation
“…A three factored structure comprised of 15 items was yielded as a result of CFA made for MBI-GS. This result yielded shows consistency with the results of similar research verifying MBI-GS's three factored structures in literature Langballe, Falkum, Innstrand & Aasland, 2006;Chirkowska-Smolak & Kleka, 2011). Moreover, it is observed that the correlation values found to range between .19 and .66 between MBI-GS's sub factors are similar to the research results in the literature Taris, Schreurs & Schaufeli 1999;Bakker, Demerouti & Schaufeli, 2002;Chirkowska-Smolak & Kleka, 2011).…”
Section: Result Discussion and Proposalssupporting
confidence: 91%
“…Buna ek olarak, güvenirlik çalışmaları kapsamında MTE-GF'nin tükenme, duyarsızlaşma ve yetkinlik alt faktörleri için sırasıyla .82, .77 ve .72 olarak elde edilen iç tutarlık katsayılarının, yine, literatürdeki benzer araştırma sonuçlarıyla Taris, Schreurs & Schaufeli 1999;Schutte vd., 2000;Bakker, Demerouti & Schaufeli, 2002;Langballe vd., 2006;Chirkowska-Smolak & Kleka, 2011) paralel olduğu görülmektedir.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified
“…niedopasowaniu jednostki i środowiska zawodowego sprzyja 6 czynników: nadmierne obciążenie pracą, brak kontroli, niewystarczające wynagrodzenie, brak wsparcia społecznego, brak sprawiedliwości i konflikt wartości [3]. Do badania tak pojmowanego wypalenia zawodowego skonstruowano kwestionariusz Maslach Burnout Inventory -General Survey (MBI-GS), który do polskich warunków zaadaptowali Chirkowska-Smolak i Kleka [18].…”
Section: Wstępunclassified
“…Thus, similar studies in different countries with diverse cultures may remove some items in their studies (31,32). This may be related to to the cultural sense of that item more than just the literal meaning just similar to the items that were excluded in the study ( ei, the item, "I'm just trying to handle my own affairs and do not do it for others.…”
Section: Discussionmentioning
confidence: 99%